Penerapan Algoritma Mifflin-St Jeor dalam Pengembangan Fitur Perhitungan Kebutuhan Kalori Harian berbasis Mobile Android - Hayati, Nuvita Nur; Mardhiyyah, Rodhiyah (Journal of Information System Research (JOSH), 2024)
Having limited knowledge about balanced nutrition for the body can be an obstacle for many people in their efforts to live a healthy lifestyle. Due to not calculating calorie intake properly, it can potentially experience conditions where daily calorie intake does not match the needs, either deficiency or excess. This research aims to develop a daily calorie requirement calculation feature and daily nutrient intake calculation that allows users to calculate the calorie and nutrient intake of foods that have been consumed every day. The algorithm applied in calculating daily calorie needs in this study is using the Mifflin-St Jeor algorithm. System design in this study uses the Unified Modeling Language (UML) with implementation using Kotlin programming language and Android Studio software. The result of this research is a daily calorie requirement calculation feature where users can calculate daily calorie requirements based on physical information data filled in by users as well as calculating daily nutritional intake by adding foods consumed, then the available features can calculate calories and nutritional content of foods that have been added by users so that users can find out how many total calories and nutritional content of foods that have been consumed by them. Calculations using the Mifflin-St Jeor algorithm resulted in the conclusion that a person's basic daily calorie needs can vary depending on body weight, height, age, and gender.